The Spanish Prioritization System for Highly Sensitized Patients: A Successful Tool. (July 2018) - Valentin, Maria; Vega, Rocio R; Martin, Carmen C; Dominguez-Gil, Beatriz B
Abstract : PATHI. : A prioritization kidney allocation system, based on virtual crossmatch, was implemented in Spain in June 2015 to broaden access to transplantation for patients with cPRA ≥98%. Participating centers must offer to the program one of the kidneys of every brain-death donor between 18–70 years old. The algorithm for recipient's selection was based on blood type compatibility and negative crossmatch by using Human leukocyte Antigens class I (A, B, C) and class II (DRB1, DQB1, DQA1). Aim: To evaluate the results of a National prioritization system based on virtual crossmatch in very high sensitized patients waiting for a kidney transplant after 18 months. Methods: Demographic and clinical characteristics were collected from every patient included in the program between June 2015 and December 2016. The number of brain death donors assigned to the program, and patients transplanted were analyzed as well as number of kidney offered and reasons for either rejecting an offer or non-proceeding with the transplant once the kidney is accepted. Outcomes of patients transplanted between June 2015 and September 2016 were also studied. Results: 786 patients with cPRA ≥98% were registered in the program. 408 (51.9%) were men and the mean age was 52.6 (12.3), median time on dialysis was 75.5 (45.7-114) months. 86.2% of patients had been previously transplanted. 879 brain death donors were assigned to the program. Virtual crossmatch was negative for 308 (35%) donors. From them, 243 kidneys were accepted and 159 transplanted (20.2% over patients included. The mean time from the registration to transplant was 158 (76–277) days. The reasons for refusal (N=163) were reasons related to the recipient (non-immunological) in 34 (36%), unacceptable antigen in 12(13%), donor pathology in 23 (24%) cases, ischemia time in 8 (9%) and age difference in 17 (18%) cases (median age difference 26 (21–35) years). After accepting the kidney, the transplant didn't proceed in 84 cases (37% due to positive real crossmatch). Outcomes were analyzed in 125 patients. Median cold ischemia time was 19 (16–22) hours. Delayed graft function was detected in 12 (9.6%). The median follow-up time was 7.4 (4–10) months. Patient and graft survival were 93.6% and 89.7% respectively. Median Creatinine level (N=109) was1.48 (1.13-1.97) mg/dl. Conclusion: The Spanish prioritization system increases transplant options for hypersensitized patients with excellent outcomes in the short term after transplantation. Non-heart beating donors or living altruistic donors could be offered to the priority allocation system to increase donor pool and transplant options.